Properties of the particle distribution in Pb–Pb collisions at sNN=5.02 TeV and sNN=2.76 TeV - Geng, Yan-Feng; Li, Bao-Chun (Frontiers in Physics, 2023)
In Tsallis statistics with a multisource production, we study the transverse momentum spectra of heavy-flavor mesons in Pb-Pb collisions at 5.02 TeV and charged particles in Pb-Pb collisions at 2.76 TeV. A good agreement can be observed between the results obtained in the model and the experimental results of ALICE and CMS collaboration. The nuclear modification factor is reproduced. Properties reflected in the multiparticle system are discussed by the parameters provided in the improved model. It is found that the temperature T and the increase with the centrality for the same particle due to the excitation degree of the multiparticle system. The nonequilibrium degree at 5.02 TeV is larger than that at 2.76 TeV. It shows that the system at the larger collision energy deviates farther from the equilibrium state. Thermodynamic properties extracted by the particle distribution can help us to understand properties of the particle distribution in high energy heavy-ion collisions from different perspectives.